"Can we have a little humanity here?": Patient perspectives on the impact of a standardized care process for patients who use opioids for the management of chronic pain. Issue 7 (July 2022) - Montag Schafer, Katherine; Pratt, Rebekah; Ricco, Jason; Brown, Kathryn
Abstract: Objective: Standardized processes have evolved in response to the opioid epidemic. The impact of standardized processes on patients has not been adequately described. Methods: Five focus groups were held at four affiliated academic family medicine clinics. All participants experienced a transition to a standardized process for their ongoing opioid use for chronic, non-cancer pain. Data was analyzed and coded using a grounded theory approach with NVivo12 (QSR International). Results: Thirty patients participated. Five main themes emerged: experience of pain; view of opioid medications; view of opioid prescribing process changes; "good patients" and trust; and experience with medical clinicians and clinics. Conclusions: Standardized processes created to improve the safety of opioid prescribing have burdened patients and resulted in a loss of trust and autonomy. Patients perceived greater risks for other patients prescribed opioids and processes are a result of their actions. Practice Implications: Healthcare systems must acknowledge patients' burden, shift away from interventions that are limited in supporting data, reinforce patient agency and shift the conversation to unsafe medications rather than supervision of "bad actors". Highlights: The use of processes to increase patient safety are a response to the opioid epidemic. Focus groups assessed their impact on patients in academic family medicine clinics. Patients experience added cost & time resultant to opioid prescribing standardization. Patients believe that standardization is due to actions of untrustworthy patients. Processes & related education should be reframed to medicines with inherent risks.